Dendritic cell–related gene signature in pancreatic cancer stratifies patient subtypes and implicates a KCTD14–TNF signaling axis - Liang, Yuxin; Gu, Yuheng; Zhang, Zilong; Zhong, Deyuan; Yan, Hongtao; Su, Yuhao; Chen, Yahui; Wang, Fei; Leng, Zhengwei; Huang, Xiaolun (Frontiers in Immunology, 2025)
BackgroundPancreatic cancer (PC) is characterized by a profoundly immunosuppressive tumor microenvironment and poor prognosis. Dendritic cells (DCs) are pivotal for antigen presentation and T-cell activation, yet their prognostic and mechanistic roles in PC remain incompletely defined.MethodsThis study performed weighted gene co-expression network analysis (WGCNA) on transcriptomic data from The Cancer Genome Atlas (TCGA) and two Gene Expression Omnibus cohorts (GSE62165, GSE85916) to identify DC–related gene modules. Consensus clustering based on these modules stratified patients into two immune phenotypes. A four-gene DC–related risk score (DCRS) was constructed using LASSO-Cox regression and validated in independent cohorts. Single-cell RNA sequencing data from 25 PC samples (GSE242230) were analyzed through cell clustering analysis, cell-cell communication analysis, and pathway-specific analysis. Functional assays following KCTD14 knockdown in CAPAN-1 and PANC-1 cell lines assessed its impact on proliferation, migration, invasion, and TNF signaling.ResultsWGCNA identified 130 overlapping DC–related genes enriched in immune pathways. Two DC–related patient clusters exhibited distinct overall survival (OS) (P < 0.05). The DCRS robustly stratified patients into high- and low-risk groups in both TCGA training and validation sets. DCRS demonstrated good predictive potential for OS and there is a significant difference in OS between the two groups of patients (P < 0.05). Single-cell analysis revealed KCTD14 enrichment in malignant epithelial cells and predicted its interaction with DCs via the TNF-TNFRSF1A axis. In vitro, KCTD14 knockdown significantly reduced PC cell proliferation, colony formation, migration, and invasion, and downregulated TNF-α and TNFRSF1A expression (P < 0.01).ConclusionWe identified a novel DC–related gene signature that stratifies PC patients by prognosis and highlights KCTD14 as a novel immunomodulatory oncogene acting through the TNF-TNFR1 axis. Our findings provide a foundation for integrating DCRS into clinical risk assessment and for pursuing KCTD14/TNFR1-targeted therapies to overcome DC-mediated immune suppression in pancreatic cancer.